Accuracy of repetition in serial movement - Bilinski, W.; Czyz, S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Control process in free movement is very complicated, indeed. Precise, or commensurate with model execution require very high regulation. In control process the most important is the effect of given task. In the midst of many characteristics determine effectiveness of move, a number of abilities are conditioned on control process [4]. Among other things is rhythmisation- one of the co-ordination abilities. Control process proceeds under similar principles, but not at everyone with the same accuracy, speed, diversity, activity, and rhythmisation. There are individual properties of control process that determine the level of co-ordination abilities. The goal of this work is to show the control process in the context of movement accuracy in groups of different rhythm ability. There was advanced the hypothesis: the individuals with high level of rhythm ability do perform the given task (cyclical movement) with better accuracy with regard to the way, speed, time performance, acceleration, than the individuals with low level of that ability. Methods 60 students were divided into 3 groups after the test estimated the level of rhythm ability, based on Jaques-Dalcroze method [2]. The groups were called: I group - "best", II - "middle", III - "worst". The second stage of experiment concerned way and acceleration measurement during exercise. In use of that searching installation was possible to measure the cyclical movement recording acceleration and way. There were calculated: Standard deviations both measured parameters superimposing graphs of consecutive trials of cyclical move. Then it was taken the average of Standard deviation. Autocorrelation - function of autocorrelation random signal describes general dependence on signal value in certain moment to signal value in different moment. From the graph of acceleration and way were read signal values after 1 second, which describe the precision of repeated move. Discussion/Conclusions There was found out, that movement`s sequences are not the same. Standard deviations (SD) were calculated from 10 repeated movements. It was assumed that, the smaller average of SD and the bigger value of autocorrelation, the move, its next repetitions, are more accurate to each other. There were found out also, that in first group, called "best" results are better, than in third group. It is presumed that rhythm skills affect the precision of cyclical move. On the other hand there were not found significant differences between individuals in all groups in case of time period at performed task. Using this kind of measurement, analysis we can also make some evaluation of rhythm ability, showing its importance in control process. We do hope that this makes possible to find new method of the estimation of rhythmisation - one of the co-ordination ability.